2015
DOI: 10.1038/jp.2015.166
|View full text |Cite
|
Sign up to set email alerts
|

Jaundice, phototherapy and DNA damage in full-term neonates

Abstract: Hyperbilirubinemia does not influence DNA damage, whereas both conventional and intensive phototherapy are associated with DNA damage in term infants with hyperbilirubinemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 29 publications
0
34
1
2
Order By: Relevance
“…It may be thought that the increase in the risk of cancer is related with the long-term results of the genotoxic effect of phototherapy or hyperbilirubinemia itself. In studies conducted with Comet assays, it was shown that phototherapy caused DNA damage in peripheral blood lymphocytes and triggered apoptosis (22,23). It would be beneficial to consider such risks when deciding upon the initiation of therapy, especially in neonates with bilirubin levels below phototherapy limits.…”
Section: Discussionmentioning
confidence: 99%
“…It may be thought that the increase in the risk of cancer is related with the long-term results of the genotoxic effect of phototherapy or hyperbilirubinemia itself. In studies conducted with Comet assays, it was shown that phototherapy caused DNA damage in peripheral blood lymphocytes and triggered apoptosis (22,23). It would be beneficial to consider such risks when deciding upon the initiation of therapy, especially in neonates with bilirubin levels below phototherapy limits.…”
Section: Discussionmentioning
confidence: 99%
“…11 Additionally, in vivo experiments on human newborns have demonstrated DNA damage, alterations in cytokine levels, and evidence of oxidative stress after treatment with phototherapy. [12][13][14][15][16][17][18][19][20][21][22] This is concerning because all these conditions have been implicated in the pathogenesis of cancer. 28,29 Although the clinical importance of these alterations remains to be elucidated, they present a potential mechanism whereby phototherapy could be related to childhood cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The potential for phototherapy to increase the incidence of cancer is supported by data from in vitro and in vivo studies. [11][12][13][14][15][16][17][18][19][20][21][22] It is important to determine whether phototherapy contributes to early childhood cancer to determine the optimal management of infants with neonatal hyperbilirubinemia. In this study, we used population-based data to investigate the association between phototherapy and cancer in the first year after birth.…”
mentioning
confidence: 99%
“…It increased significantly after exposure to phototherapy compared with prephototherapy values. The duration of phototherapy correlated positively with markers of DNA damage but the intensity of used light don't have any genotoxic impact [27] (Figure 4).…”
Section: Recents Studies Using Comest Assaymentioning
confidence: 99%